Quality of family planning services for women of reproductive age in Lao PDR. Issue 2 (30th July 2020) - Thongmixay, Souksamone; Schoneveld, Tess; Vongxay, Viengnakhone; Broerse, Jacqueline E. W.; Sychareun, Vanphanom; Essink, Dirk R.
ABSTRACT: Background: In Lao PDR, 15% of the married women want to postpone or prevent having a child, yet most are not using contraceptives to achieve this. Literature shows that usage of contraceptives is strongly dependent on the quality of family planning services. However, little is known about the quality of family planning services in Lao PDR. Objective: To assess the quality of family planning services provided in public health facilities in Lao PDR. Methods: Using a cross-sectional study design, public health facilities in three provinces in Lao PDR were assessed on structure, process and outcome measures of quality. Following the Quick Investigation of Quality approach, client exit interviews (n = 393), structured observations (n = 218) and facility audits (n = 17) were conducted. Results: Facility audits, observations and client exit interviews painted different pictures of the overall quality of family planning services. Taking all together, the quality was rated as moderate to high. Only marginal differences in quality were found between family planning services located in different geographical areas. Notably, only married women with children were using these services. Although contraceptives were provided, little attention was given to the information provided during consultations and to the interpersonal relationship between client and provider. Conclusion: The results suggest that although improvements are needed to enhance quality of individual consultations, the greatest gain in reducing unwanted pregnancies would be made by ensuring access for all women of reproductive age.